The effect of the quizizz application learning media on student learning outcomes in fikih class xi at madrasah aliyah negeri 14 jakarta - Abdul Hakam Al-Karim; Amin Fauzi (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to examine the application of Quizizz application-based learning media on the achievement of student learning outcomes in the subject of Islamic jurisprudence in class XI at the State Islamic Senior High School (MAN). This study employed a case study method where the Quizizz application was integrated into the learning process, and the learning outcomes were analyzed to assess its effectiveness and compared with learning outcomes using conventional methods.The research sample consisted of 36 eleventh-grade students from MAN 14 Jakarta. The findings revealed that the Wilcoxon test showed a significant difference between learning outcomes using the Quizizz application and conventional methods, with a p-value of 0.001 < 0.05. However, the N-Gain Score test for both learning outcomes indicated that this difference leaned towards ineffectiveness. Therefore, the use of the Quizizz application as a learning medium was not more effective compared to conventional methods.